Legal Protection of Creditors Against Letters of Undertaking as Additional Agreements - Siregar, Pascal Raja Ilham; Kanthika, I Made; Markoni; Subiyanto, Achmad Edi (GoAcademica Research & Publishing, 2024)
This research aims to learn about the Legal Protection of Creditors Against Letters of Undertaking as Additional Agreements. The research method is normative juridical, using deductive thinking and library data collection. One of them is using the Legal Protection Theory to examine problems in LoUs between debtors and creditors so that debtors commit themselves to fulfilling obligations so that they get their rights by bank rules and applicable laws and regulations in the event of payment failure or default with the conclusion of preventive and repressive measures. This research found that a Letter of Undertaking (LoU) is part of an additional agreement or accessory and an alternative third-party guarantee in the form of a statement of the promissory note to fulfil an obligation made by the Debtor. In this modern and rapidly developing era, LoUs are born as credit guarantees or financing in various fields of construction projects, infrastructure projects, and tender bonds, which are used to facilitate business to help smooth national and international trade transactions.